2018
DOI: 10.1186/s13072-018-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic DNA fragments bearing ICR cis elements become differentially methylated and recapitulate genomic imprinting in transgenic mice

Abstract: BackgroundGenomic imprinting is governed by allele-specific DNA methylation at imprinting control regions (ICRs), and the mechanism controlling its differential methylation establishment during gametogenesis has been a subject of intensive research interest. However, recent studies have reported that gamete methylation is not restricted at the ICRs, thus highlighting the significance of ICR methylation maintenance during the preimplantation period where genome-wide epigenetic reprogramming takes place. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
5
13
0
Order By: Relevance
“…First, ZFP57 binds to DNA in a CpG methylation-dependent manner, whereas the transgenic H19 ICR in sperm is unmethylated. Consistent with this, in our previous work [15], we failed to demonstrate ZFP57 binding to the 478-bp sequence in gel-shift assays. In addition, the DNA methylation status of the endogenous H19 ICR is not affected in Zfp57-knockout mice [16,18].…”
supporting
confidence: 91%
See 4 more Smart Citations
“…First, ZFP57 binds to DNA in a CpG methylation-dependent manner, whereas the transgenic H19 ICR in sperm is unmethylated. Consistent with this, in our previous work [15], we failed to demonstrate ZFP57 binding to the 478-bp sequence in gel-shift assays. In addition, the DNA methylation status of the endogenous H19 ICR is not affected in Zfp57-knockout mice [16,18].…”
supporting
confidence: 91%
“…In previous work, we have narrowed down the sequence responsible for post-fertilization paternal methylation of the H19 ICR to a 478-bp region and demonstrated that it is required in vivo for normal development ( Fig. 1a; [12,15]). Furthermore, we showed that postfertilization, allele-specific methylation was recapitulated in a λ-phage-based synthetic DNA fragment in the TgM only when the 478-bp sequence was included [15].…”
Section: A 118-bp Sequence At the 5′-segment Of The H19 Icr Is Essentmentioning
confidence: 99%
See 3 more Smart Citations